Teaching in the eyes of others: a review of teaching square group - Mhamed, A.A.S.; Gilman, C.; Schonbach, C.; Frank, A. (Nazarbayev University, 2014)
The project's main objective is to learn through peer observation. The Teaching Squares program provides faculty an opportunity to gain new insight into their teaching through a non-evaluative process of reciprocal classroom observation and self-reflection. The four faculty in each "teaching square" agree to visit each other's classes over the course of a semester and then meet to discuss what they learned from their observations.
Keywords: teaching; eyes; square group; squares program; teaching square